2019
DOI: 10.1038/s41560-019-0493-0
|View full text |Cite|
|
Sign up to set email alerts
|

Exploring the bottlenecks of anionic redox in Li-rich layered sulfides

Abstract: To satisfy the long-awaited need of new lithium-ion battery cathode materials with higher energy density, anionic redox chemistry has emerged as a new paradigm that is responsible for the high capacity in Li-rich layered oxides, for example, in Li1.2Ni0.13Mn0.54Co0.13O2 (Li-rich NMC). However, their marketimplementation has been plagued by certain bottlenecks originating intriguingly from the anionic redox activity itself. To fundamentally understand these bottlenecks (voltage fade, hysteresis and sluggish kin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

9
236
3

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 152 publications
(248 citation statements)
references
References 74 publications
(100 reference statements)
9
236
3
Order By: Relevance
“…To conquer the intrinsic issues of Oa nionic redox chemistry,replacement by less electronegative Swas recently proposed and is gaining importance since Shas been found to effectively inhibit anion loss while also showing higher reversibility with lower hysteresis during cycling. [15][16][17] Shadike et al have studied the electrochemistry of NaCrS 2 relying only on Sanionic redox chemistry by blocking the transitionmetal redox chemistry.T his material was found to provide ac apacity of 95 mAh g À1 and, although it cannot solve the issue of low capacities,i tr emains am odel sulfide redox chemistry. [15] Therefore,t he cation redox in the sulfide compounds was targeted in pursuit of perfect sulfide anion redox chemistries.W ang et al reported O3-NaCr 2/3 Ti 1/3 S 2 , which was found to deliver higher reversible capacities of 186 mAh g À1 (0.95 Na) based on cumulative,cation, and anion redox processes.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…To conquer the intrinsic issues of Oa nionic redox chemistry,replacement by less electronegative Swas recently proposed and is gaining importance since Shas been found to effectively inhibit anion loss while also showing higher reversibility with lower hysteresis during cycling. [15][16][17] Shadike et al have studied the electrochemistry of NaCrS 2 relying only on Sanionic redox chemistry by blocking the transitionmetal redox chemistry.T his material was found to provide ac apacity of 95 mAh g À1 and, although it cannot solve the issue of low capacities,i tr emains am odel sulfide redox chemistry. [15] Therefore,t he cation redox in the sulfide compounds was targeted in pursuit of perfect sulfide anion redox chemistries.W ang et al reported O3-NaCr 2/3 Ti 1/3 S 2 , which was found to deliver higher reversible capacities of 186 mAh g À1 (0.95 Na) based on cumulative,cation, and anion redox processes.…”
Section: Introductionmentioning
confidence: 99%
“…[15] Therefore,t he cation redox in the sulfide compounds was targeted in pursuit of perfect sulfide anion redox chemistries.W ang et al reported O3-NaCr 2/3 Ti 1/3 S 2 , which was found to deliver higher reversible capacities of 186 mAh g À1 (0.95 Na) based on cumulative,cation, and anion redox processes. [16] Recently,Saha et al presented fundamental research on the bottlenecks of Sr edox, [17] in which an ew material Li 1.33À2y/3 Ti 0.67Ày/3 Fe y S 2 (y = 0.3) was capable of ar eversible capacity as high as 245 mAh g À1 .T he high capacity resulted from the existence of 3d 6 electrons in the Fe 2+/3+ redox couple that activated the anionic Sr edox. During the final review stage of this manuscript, See et al revealed the electrochemistry of aL i-rich layered iron sulfide Li 2 FeS 2 , [18] whereas Zhao-Karger reported on multivalent cation storage in VS 4 , [19] further emphasizing the rising importance of this class of materials.…”
Section: Introductionmentioning
confidence: 99%
“…However, considering the complexity of the battery materials, a combination of the solid state chemistry approaches with the computational tools still remains serious assets. Among many other examples, this can be illustrated by recent discoveries of metal-ion battery cathodes triggered by the relatively simple concept of the anionic redox and its crystal chemistry expansions: the Li 2 (M,M′)O 3 (M = Ru, Ir, M′ = Ti, Sn) 15 , 16 , 69 and Li 3 IrO 4 86 oxides with the layered and framework structures, the Li-rich disordered xLi 3 NbO 4 – (1-x)LiMO 2 (or Li 2 MO 3 ) (M = Mn, Fe, Co, Ni) 87 and short-range ordered Li 1.2 Mn 0.4 M 0.4 O 2 (M = Ti, Zr) 63 rock-salt oxides and Li 1.9 Mn 0.95 O 2.05 F 0.95 oxyfluoride 88 , the Na-based Mg/Zn-doped layered oxides 17 , 22 and Na-based Li-rich layered oxides 89 , Li 1.68 Mn 0.6 O 4−x F x partially ordered spinels 90 , and, finally, the Li-rich layered Li 1.33–2y/3 Ti 0.67–y/3 Fe y S 2 sulfides 91 . However, the next step towards the materials with practical importance is clearly of high demand.…”
Section: Discussionmentioning
confidence: 99%
“…Less electronegative anions, such as chalcogenides (Ch ¼ S 2À , Se 2À ), are more easily oxidized than oxides, favoring Ch 2À anionic redox activity 11 and higher capacities. 12 The presence of highly polarizable chalcogenide anions is also a strong advantage to increase electronic conductivity, which oen limits the electrochemical properties in oxide systems.…”
Section: Introductionmentioning
confidence: 99%